2015
DOI: 10.1007/s00436-014-4285-y
|View full text |Cite
|
Sign up to set email alerts
|

New host records of three juvenile nematodes in Egypt: Anisakis sp. (Type II), Hysterothylacium patagonense (Anisakidae), and Echinocephalus overstreeti (Gnathostomatidae) from the greater lizard fish Saurida undosquamis of the Red Sea

Abstract: Three juvenile nematode parasites were collected naturally from 90 (75 %) out of 120 specimens of the marine greater lizard fish Saurida undosquamis captured from water coasts at Hurghada City along the Red Sea in Egypt during the period from September 2013 to April 2014. Worms were identified on the basis of light and scanning electron microscopy. Two of the recovered worms were isolated from the peritoneal cavity of the infected fish around the wall of the stomach as encapsulated larvae. The anisakid juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…In the present study, larvae were isolated from P. pagrus intestine. Also, it was found in Saurida undosquamis (Morsy et al, 2015). The present morphology agreed with the descriptions of E. overstreeti of Deardorff and Ko (1983) in presence of very narrow lateral alae, simple pseudolabia, two well-developed papillae and amphid, small rounded interlabia, cephalic bulb and arranged spines.…”
Section: Introductionsupporting
confidence: 91%
“…In the present study, larvae were isolated from P. pagrus intestine. Also, it was found in Saurida undosquamis (Morsy et al, 2015). The present morphology agreed with the descriptions of E. overstreeti of Deardorff and Ko (1983) in presence of very narrow lateral alae, simple pseudolabia, two well-developed papillae and amphid, small rounded interlabia, cephalic bulb and arranged spines.…”
Section: Introductionsupporting
confidence: 91%
“…Also, it was higher than (33.7%) by Debenedetti et al (2019) in At-lantic and Mediterranean Regions; they reported that larvae were higher in viscera than musculature. But, Morsy et al (2015) recorded 3 juvenile nematodes; Anisakis sp.…”
Section: Introductionmentioning
confidence: 99%
“…Rizk et al (2015) reported it some marine fish in Damietta. Morsy et al (2015) recorded three juvenile nematodes: Anisakis Hysterothylacium patagnense and Echinocephalus overstreeti from Saurida undosquamis in the Red Sea. Younis et al (2017) found Contracaecum larva from teleostean species in Lake Nasser.…”
Section: Introductionmentioning
confidence: 99%
“…Heavily infected fish show emaciation, imbalanced swimming, and reduction of their vitality (Klimpel et al 2011;Mehlhorn et al 2011;Morsy et al 2013Morsy et al , 2015Abdel-Ghaffar et al 2014. The consumption of raw or undercooked fish may lead to infection with several helminthes.…”
Section: Introductionmentioning
confidence: 99%